Ankle ligament reconstruction after wide resection of the osteosarcoma of the distal fibula: A case report - Tanawat Vaseenon (2018)
© 2017 The Author(s). Background: Restoration of the lateral ankle after distal fibulectomy is a difficult reconstructive procedure. Many surgical techniques have been proposed. This report shows another fibular reconstructive option with promising outcome. Case presentation: We report the case of a 30-year-old woman who presented with a solitary mass located in the lateral aspect of the ankle. The mass had grown rapidly for 2 months and caused increasing pain. Physical examination showed a 3.0 cm diameter tender, nonmobile hard mass in the lateral malleolus. Radiographs showed an osteolytic lesion involving the lateral cortex at the distal fibula. After incisional biopsy, pathologic examination found a well-differentiated intramedullary osteosarcoma. Neoadjuvant chemotherapy with doxorubicin was provided for 3 months prior to definitive surgical treatment. Magnetic resonance imaging showed persistent tumor in the biopsy site. After distal fibulectomy and wide resection, split tibialis posterior tendon transfer to the remaining peroneus brevis restored the stability of the ankle. The pain resolved within 3 months. The ankle was stable and no recurrence of the cancer was found at a 7 year follow-up. Conclusion: Reconstruction following distal fibulectomy and surrounding soft tissue resection responds favorably to split tibialis posterior transfer to the remaining peroneus brevis suggesting that this technique can provide a good and functional outcome.